Community-based tourism in the context of the neoliberal paradigm: counter-hegemonic initiatives and land disputes in northeastern Brazil - Ilana Barreto Kiyotani; Wagner Fernandes Costa; Maria Aparecida Pontes da Fonseca (Via@)
In the context of the neoliberal model, the expansion of tourism has been promoted by prioritizing market structures, supporting large businesses and often sidelining initiatives focused on social justice and equitable income distribution. Community-based tourism (CBT), in contrast, is seen as a counter-hegemonic practice aiming for greater socio-economic equity, unlike its conventional counterpart. This study aims to analyze the motivating factors and action strategies behind the development of CBT in Chã de Jardim, Doces Tambaba, and Porto do Capim in Paraiba State (northeastern Brazil). The methodology involved analyzing documents on public tourism policies, gathering data from non-governmental organizations and digital platforms, and conducting interviews. Despite challenging conditions, it was concluded that CBT is gaining visibility in Brazil. In the contexts examined, it represents counter-hegemonic actions, serving as a strategy to ensure land tenure.